ANALYZING FACTORS THAT DRIVE IMPUSLIVE BUYING BEHAVIOR TOWARD FASHION PRODUCTS IN MANADO TOWN SQUARE - Lontoh, Nathania .; Saerang, David P.E; Tielung, Maria V.J (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
Abstract: The fashion industry has a great influence and is a significant driver in Indonesia’s creative economy. Manado Town Square is the social and shopping center of Manado; therefore, it presents a huge opportunity for marketers to provoke impulsive buying behavior of consumers. This research aims to analyze and define the factors that drive impulsive buying behavior toward fashion products in Manado Town Square. Knowing these factors, marketers can enhance and take advantage of these factors in order to instigate consumers to purchase more items than planned generating more revenue. In order to define these factors this research takes a quantitative approach by obtaining data through questionnaires using convenience sampling in which 100 buyers of fashion products in Manado Town Square are the respondents. To analyze the data this research uses Factor Analysis as the research method. There are 20 variables included in the analysis, and the results show that 19 variables correlate with the other factors. From the results of the factoring process there are 5 factors formed which are: Environmental Factors, Multisensory Atmospheric Stimuli Triggering Mood and Emotion, Promotional Techniques, Situational Factors and Marketing Strategies. Marketers should take advantage of these factors to trigger consumers’ impulsive buying behavior.  Keywords: fashion products, impulsive buying behavior, factor analysis